68 CHIRAL SEPARATION OF THE INOTROPIC AND CHRONOTROPIC ACTIONS OF DIGOXIN. (1st March 2005) - Somberg, J. C.; Lin, C.; Cvetanovic, I.; Ke, X.; Molnar, J.; Ranade, V.
Abstract : Background: Digoxin (D) prolongs conduction at the AV node and augments cardiac contractility by inhibition of Na+, K+-ATPase. The digoxin molecule is chiral having asymmetries at the C3 and C17 carbon centers that could give rise to stereoscopic isomers. The actions of D on cardiac conduction and contractility could be mediated through the different isoforms of Na+, K+-ATPase that exist with different isomers having different degrees of inhibition of the different isoforms. Methods: Using cyclobond chiral column we separated digoxin into two distinct chromatographic peaks each with different retention times. Optical rotation was +17° and +3° respectively for the two peaks but both isolates showed the same mass/change ratio of 780, identical to that of racemate digoxin. The effects of the isolates on cardiac contractility and AV conduction were evaluated in anesthetized guinea pigs (GP): 15 GPs were randomly given D, isolate 1 or 2. AV conduction was assessed by measuring PR interval and contractility by a Walton Brody strain gauge arch sutured to the left ventricular free wall. D or the isolates were infused continuously at 6 μg/kg/min. Results: D and isolate 1 caused a progressive increase in the PR interval while isolate 2 did not progressively increase PR. D and isolate 2 caused a progressive increase in contractility (% change from the baseline) while isolate 1 caused little change in contractility. Conclusions: We concluded that D can be chirally separated with one isolate causing progressive PR prolongation and the other contractile augmentation. (Figure )